Marketing relacji w gminie - Krakowiak, Monika (Relationship Marketing in a Commune (Communal Units), 2006)
Competition of the environment, complexity and changes in the economic process, that evolve of the representative democracy through to democracy based on the dialog create a special role of the information, communication and knowledge.Integration of local commune can create quite stable relations, which are based on the roles and assumes of partner marketing.This paper presents the field research results which concerned the attitudes towards relationship marketing in communal units.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 473-479